Traffic Forecasts Ignoring Induced Demand: a Shaky Fundament for Cost-Benefit Analyses - Næss, Petter; Nicolaisen, Morten Skou; Strand, Arvid (European Journal of Transport and Infrastructure Research, 2012)
Although the phenomenon of induced traffic has been theorized for more than 60 years and is now widely accepted among transport researchers, the traffic-generating effects of road capacity expansion are still often neglected in transport modelling. Such omission can lead to serious bias in the assessments of environmental impacts as well as the economic viability of proposed road projects, especially in situations where there is a latent demand for more road capacity. This has been illustrated in the present paper by an assessment of travel time savings, environmental impacts and the economic performance of a proposed road project in Copenhagen with and without short-term induced traffic included in the transport model. The available transport model was not able to include long-term induced traffic resulting from changes in land use and in the level of service of public transport. Even though the model calculations included only a part of the induced traffic, the difference in cost-benefit results compared to the model excluding all induced traffic was substantial. The results show lower travel time savings, more adverse environmental impacts and a considerably lower benefit-cost ratio when induced traffic is partly accounted for than when it is ignored. By exaggerating the economic benefits of road capacity increase and underestimating its negative effects, omission of induced traffic can result in overallocation of public money on road construction and correspondingly less focus on other ways of dealing with congestion and environmental problems in urban areas.